Girls' Schools in Sri Lanka: Affect and Intersectionality in Religious and Gendered Identities - Albrecht, Jessica A. (Implicit religion, 2023)
This article uses the case study of Sri Lankan women who went to Buddhist and Christian middle-class girls' schools in Colombo and Kandy to examine the influence of affect on their intersectional lives. I use the theories of Judith Butler and Sara Ahmed on affect. Affects, they agree, emerge within the brinks of contact, it is the process of being acted upon (being affected) and acting on (affecting) - affect is a specific form of relation. This article interwaves the ethnographic findings with the theoretical discussions to progressively build on it and show precisely the relations between affect, language and intersectional identities. Buddhist and Muslim girls’ voices and experiences at middle-class girls' schools in Sri Lanka will be examined from an intersectional perspective. I propose to think of affect as the binding glue of the frames of our intersectional identities.